Borophene via Micromechanical Exfoliation. Issue 34 (16th July 2021) - Chahal, Sumit; Ranjan, Pranay; Motlag, Maithili; Yamijala, Sharma S. R. K. C.; Late, Dattatreya J.; Sadki, El Hadi S.; Cheng, Gary J.; Kumar, Prashant
Abstract: Borophene, the lightest among all Xenes, possesses extreme electronic mobility along with high carrier density and high Young's modulus. To accomplish device‐quality borophene, novel approaches of realization of monolayers need to be urgently explored. In this work, micromechanical exfoliation is discovered to result in mono‐ and few‐layered borophene of device quality. Borophene sheets are successfully fabricated down to monolayer thickness. Distinct crystallographic phases of borophene viz. XRD study reveals crystallographic phase transition from rhombohedral to several other eigen phases of borophene. The role of the destination substrates is held crucial in determining the final phase of the transferred sheet. The exfoliation energy is calculated by density functional theory. Molecular dynamics simulations are used to simulate the exfoliation process. Heterolayers of borophene, with black phosphorene (BP) or with molybdenum disulfide (MoS2 ) atomic sheets, are found to result in photoexcited coupling quantum states. Gold‐coated borophene bestows promising anchoring capability for surface‐enhanced Raman spectroscopy (SERS). Successful demonstration of the electronic behavior of micromechanically exfoliated borophene and excitonic behavior of borophene‐based heterolayers will guide future generation devices not only in electronics and excitonics, but also in thermal management, electronic packaging, hydrogen storage, hybrid energy storage, and clean energy solutions. Abstract : Micromechanical exfoliation of borophene and transfer to arbitrary substrates are experimentally demonstrated, with molecular dynamics simulation providing further validation. While high‐resolution electron imaging provides an atomistic glimpse of the crystallographic phases of borophene, Raman and XPS spectral data establish its chemical phase purity. When heterolayered with gold, borophene exhibits SERS‐based molecular sensing. Borophene‐based heterolayered excitonic devices are thus demonstrated.